A Study of Academic Oral Presentation Anxiety and Strategy Employment of EFL Graduate Students - Shiauping Tian; Masykur Mahmud (Indonesian Journal of EFL and Linguistics, 2018)
This study investigates the factors contributing to academic oral presentation anxiety, explore the differences between English majors and non-English majors in their strategy employment for academic oral presentations, examine the relationship between academic oral presentation anxiety and strategy employment, and compare the differences in oral communication strategy employment between high-anxiety and low-anxiety students. A total of sixty-one participants participated in this study by answering two questionnaires: Personal Report of Public Speaking Anxiety (PRPSA) (McCroskey, 1970) and Oral Communication Strategy Inventory (OCSI) (Nakatani, 2006), and a follow-up interview was conducted focusing on high and low-anxiety students as defined by the result on PRPSA. Results showed that the three major sources of anxiety related to content of presentation, oral proficiency, and delivery skill. Moreover, a significant difference was found in the use of Social Affective strategies between English majors and non-English majors. Besides, negative significant correlations were found in the use of Message Abandonment strategies and Attempt to Think in English strategies. Furthermore, a statistically significant difference was found in the use of Message Abandonment strategies between high-anxiety and low anxiety-students. Pedagogical implications for reducing anxiety in academic oral communication were discussed.